Grace the glitter fairy - Meadows, Daisy; Ripper, Georgie (London : Orchard Books, 2016)
Grace the Glitter Fairy can't bring a sparkle to the birthday without her magic party bag of balloons. But Rachel and Kirsty have a bright idea to keep Grace's glittery bag safe from Jack Frost.
5+.
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction